2023
DOI: 10.3390/diagnostics13122078
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Limitations of Ultrasound as a Screening Test for Ovarian Cancer

Abstract: Ovarian cancer (OC) is the seventh most common malignancy diagnosed among women, the eighth leading cause of cancer mortality globally, and the most common cause of death among all gynecological cancers. Even though recent advances in technology have allowed for more accurate radiological and laboratory diagnostic tests, approximately 60% of OC cases are diagnosed at an advanced stage. Given the high mortality rate of advanced stages of OC, early diagnosis remains the main prognostic factor. Our aim is to focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Additionally, this exam can be performed preoperatively in the evaluation of an ovarian tumor. However, despite a satisfactory sensitivity for diagnosing ovarian cancer, its low PPV limits its implementation and results frequently in unnecessary procedures or concerns [71]. In fact, the distinction between benign and malign ovarian findings is challenging.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Additionally, this exam can be performed preoperatively in the evaluation of an ovarian tumor. However, despite a satisfactory sensitivity for diagnosing ovarian cancer, its low PPV limits its implementation and results frequently in unnecessary procedures or concerns [71]. In fact, the distinction between benign and malign ovarian findings is challenging.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…[6] The efficacy of ultrasonographic assessment is limited by an early time of detection, visibility constraints and the operator's experience. [11] CA125 is currently regarded as the most dependable biomarker for ovarian cancer, but its sensitivity varies from 50% to 62%, and its specificity ranges from 73% to 77%. [12] In contemporary practice, it is primarily used as a component of multivariate algorithms, such as ROMA, RMI, or OVA1, all aimed at increasing its effectiveness.…”
Section: Surveillancementioning
confidence: 99%
“…Research has shown that IOTA's models and guidelines can significantly improve the specificity and sensitivity of ultrasound in distinguishing between benign and malignant masses. By providing a structured approach to the ultrasound-based assessment of ovarian masses, IOTA's contributions offer a valuable resource for clinicians and sonographers, aiding in more accurate and consistent diagnoses [ 55 ]. IOTA researches to refine its models and guidelines and offers training programs to promote their widespread and consistent use in clinical practice.…”
Section: Reviewmentioning
confidence: 99%